Establishment of a Novel dsRed NOD/Scid Mouse Strain to Investigate the Host and Tumor Cell Compartments. (1st May 2013) - Jacobsen, Hege Karine; Sleire, Linda; Wang, Jian; Netland, Inger Anne; Mutlu, Ercan; Førde, Hilde; Pedersen, Paal-Henning; Gullberg, Donald; Enger, Per Øyvind
<x xml:space="preserve">Abstract</x> Here we describe a NOD/Scid mouse strain expressing the dsRed transgene. The strain is maintained by inbreeding of homozygous dsRed NOD/Scid siblings, and expresses red fluorescence from various organs. The model allows engraftment of human tumor tissue, and engrafted tumors were separated into stromal and malignant cell compartments. Furthermore, we compared tumor-associated and normal fibroblast for expression of fibroblast-associated markers, and identified a marker panel that was upregulated in the tumor-associated fibroblasts. In conclusion, we propose that this model may be used in a variety of studies of tumor progression and to elucidate the role of the tumor microenvironment.